Rising Medication Prices in Pakistan: A Growing Concern for Regular Treatment Adherence - Amir Sultan; Usama Siddique; Muhammad Asif (Journal of the Pakistan Medical Association, 2026)
Access to affordable medication is essential for effective healthcare, particularly for chronic illness management. However, recent price increases in Pakistan threaten this access, raising concerns about adherence to treatment.1 Cost-related medication non-adherence is the inability to follow prescribed medication regimens due to financial constraints. Key predictors include high out-of-pocket costs, limited financial resources, lack of insurance, younger age, and poorer health. Cost-related medication nonadherence is a major barrier to effective treatment, particularly in developing countries like Pakistan, where reliance on out-of-pocket spending for medications is prevalent compared to developed nations with comprehensive healthcare systems.2 The availability and high cost of essential medicines remain significant barriers, affecting many low-income patients. These medicines are vital for meeting healthcare needs, as highlighted by Sustainable Development Goal 3.8, which emphasizes the need for accessibility to safe and affordable medications and vaccines for all. Ensuring sufficient access to medications is crucial for improving patients' quality of life.3 Continued...